Modeling and Simulation of Count Data. (13th August 2014) - Plan, EL
Abstract : Count data, or number of events per time interval, are discrete data arising from repeated time to event observations. Their mean count, or piecewise constant event rate, can be evaluated by discrete probability distributions from the Poisson model family. Clinical trial data characterization often involves population count analysis. This tutorial presents the basics and diagnostics of count modeling and simulation in the context of pharmacometrics. Consideration is given to overdispersion, underdispersion, autocorrelation, and inhomogeneity. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e129; doi:10.1038/psp.2014.27 ; published online 13 August 2014